Apoptotic effect on HeLa Cells produced by Chlamydia trachomatis-LPS - Millán-Mendoza Beatriz; Hakimi Hamid; Eley, Adrian (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2007)
Abstract: The interaction between the lipopolysaccharide (LPS) of Chlamydia trachomatis and mammalian cells is still largely unknown. Chlamydia trachomatis is an obligate intracellular bacterium responsible for several diseases in humans and animals. In this work, thanks to the isolation of the lipopolysaccharide from two serovars of Chlamydia trachomatis (LGV1-LGV2) and using a nuclear supravital fluorescent stain (Hoechst 33258), it was possible to investigate the apoptotic effect on HeLa cells. This work shows the apoptotic effect on HeLa cells when they were exposed to C. trachomatis-LPS from two serovars at concentrations equal to or higher than 0.5 µg/mL for a period of 48h. and also the lack of cellular response in the absence of C. trachomatis-LPS or in the presence of LPS obtained from other bacteria. Additionally, the use in equal conditions of polymyxin B, known as an inhibitor of bacterial LPS, showed a decrease of the apoptotic effect in such cells indicating that the cellular response observed was produced by C. trachomatis-LPS. These results support the theory that the LPS from C. trachomatis could be responsible for the toxic effect on cervical cells infected by these bacteria. Resumen: La interacción entre el lipopolisacárido (LPS) de Chlamydia trachomatis y las células de mamíferos permanece sin ser dilucidado. Chlamydia trachomatis es una bacteria intracelular responsable de diversas enfermedades en los humanos y animales. En este trabajo mediante el aislamiento del lipopolisacárido de dos serovares de Chlamydia trachomatis (LGV1-LGV2) y usando una coloración Supravital fluorescente (Hoechst 33258) fue posible investigar la respuesta de las células HeLa. El efecto apoptótico que sufren este tipo de células fue visible cuando fueron expuestas a dicho LPS en concentraciones iguales o mayores que 0,5 µg/mL por un periodo de 48 horas, sin embargo, se observó la falta de respuesta celular en su ausencia o en presencia de LPS de otras bacterias. Adicional mente, el uso en iguales condiciones de polimixina B conocido como un neutralizador de la acción del LPS demostró una disminución del efecto apoptótico en dichas células, indicando que la respuesta celular observada fue producida por C. trachomatis-LPS. Los resultados de este trabajo le dan fuerza a la teoría de que el LPS de C. trachomatis pudiera ser el responsable del efecto tóxico que se observa sobre las células cervicales infectadas con esta bacteria intracelular.